Physiological and Biochemical Effects of Diabetic Ketoacidosis in Hypertensive Male and Female Individuals. A Cross Sectional Comparative Study - Kamran Arzoo, Shaista Hussain, Hasan Akbar Khan, Muhammad Waqas Khan, Uzma Hameed, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of this study were to observe the physiological and biochemical changes in hypertensive diabetic patients with diabetic ketoacidosis. Dehydration and hypertension in diabetic patients may cause severe diabetic ketoacidosis. A remarkable significant(p<0.05) changes of random blood glucose, systolic blood pressure, diastolic blood pressure, urine ketone and dehydration levels in Group B and Group C were observed as compared to Group A.